"I think this is maybe our Achilles heel…" exploring GPs' responses to young people presenting with emotional distress in general practice: a qualitative study. Issue 9 (5th September 2013) - Roberts, Jane H; Crosland, Ann; Fulton, John
Abstract : Objective: An exploratory study to investigate general practitioners' (GPs') views and experiences of consulting with young people (aged 12–19 years) presenting with emotional distress in general practice. Design: A qualitative study using grounded theory and situational analysis. Empirical data were generated through in-depth interviews based on a topic guide developed from the literature, and augmented with a series of situational maps. Continuous field notes and theoretical memos were recorded during data collection and analysis. The data were analysed using the constant comparative method of grounded theory. There were three levels of analysis. The first level developed the open codes and is presented here. Setting: 18 general practices located in the north east of England. The practices recruited included rural, urban and mixed populations of patients who were predominantly living in socioeconomically disadvantaged communities. Participants: 19 GPs (10 women) aged between 29 and 59 years participated. The modal age range was 40–49 years. Theoretical sampling was used to guide recruitment and continued until theoretical saturation was reached. Results: The overarching finding was that anxiety about practice dominated clinical consultations involving young people presenting with emotional distress. GPs responded differently to anxiety and to related uncertainties about professional practice, independent of GP age or gender. Anxiety occurred in the consultation, at an external level, across disciplinary boundaries, in relation to communication with young people and secondary to the complexity of presentations. Conclusions: Adolescent emotional distress presents professional challenges to GPs who feel ill-equipped and inadequately prepared to address early need. Medical education needs to prepare doctors better. More research is needed to look at what factors facilitate or prohibit greater GP engagement with emotionally distressed young people.